ORGANOGENESIS TANAMAN JERUK KEPROK (CITRUS NOBILIS LOUR.) SECARA IN VITRO PADA MEDIA MS DENGAN PENAMBAHANBERBAGAI KONSENTRASI IAA (INDOLE ACETID ACID) DAN BAP (BENZYL AMINO PURIN) - Harliana, Harliana; Weaniati, Weaniati; Muslimin, Muslimin; Suwastika, I Nengah (Natural Science: Journal of Science and Technology, 2012)
Research on"Organogenesis of Tangerine orange (Citrus nobilisLour) onMSmediumsupplemented withvariousconcentrations ofIAAandBAP," has been performedatthe Tissue CultureLaboratory ofthe Faculty ofForestry, Tadulako University, Palu during the period of January andMay 2012. The goal of this study was to determine the optimum growth factor combination of IAA and BAP in MS based medium, for organogenesis of the plant. This research was arranged on Completely RandomizedDesign(CRD) withsix treatments and three replications. Growth factor combinations tested in this study were:  0.1ppm IAA + 0.4ppmBAP(C1), 0.1ppm IAA + 0.6ppm BAP(C2), 0.1ppmIAA+0.8ppmBAP(C3), 0.1ppm IAA + 1.0ppmBAP(C4), 1.0ppm IAA + 0.6ppmBAP(C5), and1.0ppmIAA+1.0ppmBAP(C6). The result indicating that the best organogenesis of Orange explant was in MS medium supplemented with 0.1 ppm IAA and 1.0 ppm BAP (C4). This medium was suitable in inducing shoot and leaf, faster than its in other medium. Explant on this medium was also produced higher number of leaves than it on other treatments.